2018
DOI: 10.1101/307629
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Patterning of a telencephalon-like region in the adult brain of amphioxus

Abstract: The evolutionary origin of the vertebrate telencephalon remains unsolved. A major challenge has been the identification of homologous brain parts in invertebrate chordates. Here we report evidence for a telencephalic region in the brain of amphioxus, the most basally branching invertebrate chordate. This region is characterised, like its vertebrate counterpart, by the combined expression of the telencephalic markers FoxG1, Emx and Lhx2/9. It is located at the anterior neural border and dorsal-ventrally pattern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 41 publications
2
3
0
Order By: Relevance
“…In order to test such hypothesis, we pharmacologically arrested proliferation, at the time when this early regionalisation of the brain starts, coinciding with the time at which proliferation resumes and restricts to the cerebral vesicle (and chordoneural hinge posteriorly). We found that localised proliferation in the amphioxus brain is necessary to generate the anterior serotonergic cells of the frontal eye complex, as we previously proposed (Benito-Gutiérrez et al, 2018). In stark contrast, we found that glutamatergic neurons, including those anterior cells associated to the frontal eye complex, remain in place despite the absence of proliferation.…”
Section: Discussionsupporting
confidence: 84%
“…In order to test such hypothesis, we pharmacologically arrested proliferation, at the time when this early regionalisation of the brain starts, coinciding with the time at which proliferation resumes and restricts to the cerebral vesicle (and chordoneural hinge posteriorly). We found that localised proliferation in the amphioxus brain is necessary to generate the anterior serotonergic cells of the frontal eye complex, as we previously proposed (Benito-Gutiérrez et al, 2018). In stark contrast, we found that glutamatergic neurons, including those anterior cells associated to the frontal eye complex, remain in place despite the absence of proliferation.…”
Section: Discussionsupporting
confidence: 84%
“…We found that localised proliferation in the amphioxus anterior brain is necessary to generate the anterior serotonergic cells of the frontal eye complex, as we previously proposed ( Benito-Gutiérrez et al, 2018 ). These neurons are born from progenitors proliferating between the 6 and 7 ss stage.…”
Section: Discussionsupporting
confidence: 84%
“…In addition to the frontal eye complex of the cerebral vesicle, VGlut ‐expressing neurons in the CNS are only found in young larvae in the primary motor center and in association with the first pigment spot (Lacalli, 1996; Lacalli & Candiani, 2017). More develop in the dorsal pre‐infundibular part of the cord as the larvae mature and metamorphose, in a region now thought to be a homolog of the vertebrate telencephalon (Benito‐Gutiérrez et al, 2018). The glutamatergic neurons of the amphioxus primary motor center have been identified as the third set of large paired neurons (the LPN3s, Lacalli & Candiani, 2017).…”
Section: Discussionmentioning
confidence: 99%